Paradigm shift in head and neck oncology patient management - Chiquit van Linden van den Heuvell; Florence van Zuuren; Mary Wells; Geert van der Laan; Harry Reintsema (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective This article describes a paradigm shift in what is considered to be good care for patients living with and after (head and neck) cancer. HNO patients often experience severe and difficult physical and psychosocial problems due to the nature and location of the disease. Many disciplines are involved in their treatment, so their voice is only one amongst many others in the decision making process. For this patient group it seems complicated to put the concept of Shared Decision Making into practice. As a step in this direction, patient reported outcomes which ask patients to select the disconcerting issues and symptoms can be used as a basis for referral, supportive care and treatment decision making. We need to provide more tailored and personalized information that is specific to individual circumstances, preferences and concerns and focuses more on the impact of treatment and access to help and support. Follow up of these patients should be concentrated on both medical and emotional aspects. Practice implications A shift in the way caregivers provide their information contributes to a more profound involvement of patients in treatment decisions.